Pengembangan Modul Berbasis Masalah Menulis Naskah Drama Siswa Kelas VIII SMP N 4 Siak Hulu Kabupaten Kampar - Suriadiman, Noprieka (GERAM, 2019)
Teaching writing skill is one form of teaching language skills that must be mastered by students. One of the important writing activities carried out by students in school is the skill of drama scripts writing. However, in learning material for writing scripts, there were still many students learning outcomes that did not meet the KKM. The weakness of students in writing drama scripts was caused by various factors, such as the technique or approach used by the teacher was not appropriate and the learning materials provided were inadequate for students. So that the aim of the study was to produce a problem-based module in the learning of drama scripts writing. Further, the research subjects were eighth-grade students of SMPN 4 Siak Hulu amounting 36 students. The results of this study were valid, practical, and effective problem-based modules for eighth-grade students for learning drama scripts writing. It was also evidenced by the value of module validity of 91.41% with very valid criteria. The module practicality value was 83.82% with very practical criteria, while module practicality by students was 78.27% with practical criteria. Additionally, the effectiveness of the module consists of students’ evaluating the overall activity was 88.33% with very high criteria or very successful. On the other hand, the overall assessment of drama script writing was 84.04 with good qualifications.